2020
DOI: 10.1055/s-0040-1712468
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis and Long-Term Results of Various Septal Extension Graft Types

Abstract: Shape, tip projection, and position can be controlled by the use of septal extension grafts (SEG). A retrospective cohort study of patients undergoing primary and secondary rhinoplasty was reviewed. The purpose of this study was to analyze maintenance of nasal length, dorsal length, and nasolabial angle postoperatively comparing different types of SEG using standardized photography and digital measurement. Two-hundred twenty-one patients undergoing rhinoplasty were included. There was a statistically significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…Brandstetter et al and Caughlin et al have shown that the long-term result does not depend on the individual technique of graft fixation: the side-to-side fixation, end-to-end fixation with unilateral splinting (perpendicular plate or thinned ethmoid bone), end-to-end fixation with extended spreader grafts, and with polydioxanone absorbable plates. 16,17 The nasolabial angle reduced 2.2 degrees from the position 2 weeks postoperative, 16 attributed to postoperative swelling, without changes in the dorsum and nasal length or tip projection after long-term follow-up. 16,17 For esthetic outcomes of secondary cleft rhinoplasty, the aims are to improve the nasal profile and nasal form on the frontal profile view.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Brandstetter et al and Caughlin et al have shown that the long-term result does not depend on the individual technique of graft fixation: the side-to-side fixation, end-to-end fixation with unilateral splinting (perpendicular plate or thinned ethmoid bone), end-to-end fixation with extended spreader grafts, and with polydioxanone absorbable plates. 16,17 The nasolabial angle reduced 2.2 degrees from the position 2 weeks postoperative, 16 attributed to postoperative swelling, without changes in the dorsum and nasal length or tip projection after long-term follow-up. 16,17 For esthetic outcomes of secondary cleft rhinoplasty, the aims are to improve the nasal profile and nasal form on the frontal profile view.…”
Section: Discussionmentioning
confidence: 95%
“…16,17 The nasolabial angle reduced 2.2 degrees from the position 2 weeks postoperative, 16 attributed to postoperative swelling, without changes in the dorsum and nasal length or tip projection after long-term follow-up. 16,17 For esthetic outcomes of secondary cleft rhinoplasty, the aims are to improve the nasal profile and nasal form on the frontal profile view. 18 Key maneuvers include centralizing the anterocaudal septum; providing structural support and/or spreader graft for nasal airway; chondromucosal advancement of the LLC with interdomal and intercartilaginous sutures, lateral crural strut; and/or alar base repositioning.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations